2020
DOI: 10.1002/edm2.145
|View full text |Cite
|
Sign up to set email alerts
|

The association of sodium‐glucose cotransporter 2 inhibitors with cancer: An overview of quantitative systematic reviews

Abstract: Aims To summarize reported cancer events associated with SGLT‐2 inhibitors used in patients with type 2 diabetes mellitus, as well as assess the quality of included reviews. Materials and methods In May 2019, we searched PubMed, Embase and the Cochrane Library for quantitative systematic reviews assessing the safety of SGLT‐2 inhibitors. Data were abstracted using a standardized form, and methodological quality was assessed using the AMSTAR 2 tool. Main outcome measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…This meta-analysis showed neither a significant association between SGLT-2i and the overall risk of malignancy in T2D patients nor with medication duration, consistent with the results of previous analysis ( 11 , 93 , 94 ). In different types of SGLT-2i analyses, we found that ertugliflozin significantly increased overall malignancy incidence, had no statistically significant difference compared to other hypoglycemic drugs or placebo alone, and had no great risk of a specific malignant tumor.…”
Section: Discussionsupporting
confidence: 88%
“…This meta-analysis showed neither a significant association between SGLT-2i and the overall risk of malignancy in T2D patients nor with medication duration, consistent with the results of previous analysis ( 11 , 93 , 94 ). In different types of SGLT-2i analyses, we found that ertugliflozin significantly increased overall malignancy incidence, had no statistically significant difference compared to other hypoglycemic drugs or placebo alone, and had no great risk of a specific malignant tumor.…”
Section: Discussionsupporting
confidence: 88%
“…These results are in line with that of the present study, which also demonstrated the superiority of dapagliflozin and ertugliflozin in relation to cancer risk. Such findings are further emphasized by that of Pelletier et al, which also failed to display an increased cancer risk with SGLT2I users, regardless of cancer type (28). However, the obscurity in the findings concerning SGLT2I primarily resides in the fact that the malignancy risk varies depending on the SGLT2I and cancer subtypes.…”
Section: Discussionmentioning
confidence: 88%
“…The protocol for this study is registered with the PROSPERO international prospective register of systematic reviews (PROSPERO 2019: CRD42019135863). 14…”
Section: Methodsmentioning
confidence: 99%